Segurança do paciente: análise das notificações de eventos em um hospital privado - Melchiades, Ediana Preisler [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Patient safety and risk management are key requirements for strengthening the management process in the organization. This study aimed to identify and analyze events reported to the Patient Safety Unit in a private hospital in the state of São Paulo, Brazil. It is a descriptive, exploratory study, retrospective with a quantitative data analysis of the events related to assistance and involving health products, from January to December 2014. Seven hundred and eleven (711) notifications related to patient care and health care products were analyzed . The time analysis of the notifications related to care processes was significantly higher than that of direct patient care. The units that received most event notifications were: Surgical I and II (23.63 %), Adult Intensive Care Unit (17.30%), Pharmacy (11.11%) and Internal Medicine (10.27 %). Most reported event groups were: medication error (14.21%), loss of nutritional probe (13,22 %) and skin lesions (11.95 %). The positions that most reported events of the direct assistance group to the patient and care process were: nursing care coordinator and nurse. It can be concluded that the notification of events related to patient care and involving health products is fundamentally important within the institution and contributes to the adoption of incident prevention strategies and improvement of the quality of the provided care. From the research, we developed two products to be adopted in the institution involved : a) Patient Safety Plan , in accordance with the requirements of the official directives (DRC number 36 of July 25, 2013) b ) Risk Management Matrix per unit based on the Healthcare Failure Mode and Effect Analysis (HFMEA) methodology.

A segurança do paciente e o gerenciamento de riscos são requisitos fundamentais para fortalecimento do processo de gestão na organização. O presente estudo teve como objetivo principal identificar e analisar eventos notificados ao Núcleo de Segurança do Paciente em hospital privado do Estado de São Paulo, Brasil. Trata-se de um estudo descritivo, exploratório, retrospectivo com análise quantitativa dos dados dos eventos relacionados à assistência e envolvendo produtos de saúde, no período de janeiro a dezembro de 2014. Foram analisadas 711 notificações relacionadas à assistência ao paciente e produtos de saúde. O tempo de análise das notificações relacionadas a processos assistenciais foi significativamente maior que o da assistência direta ao paciente. As unidades que mais receberam notificações de eventos foram: Cirúrgicas I e II (23,63%), Unidade de Terapia Intensiva Adulto (17,30%), Farmácia (11,11%) e Clínica Médica (10,27%). Os grupos de eventos mais notificados foram: erro de medicação (14,21%), perda de sonda nutricional (13,22%) e lesão de pele (11,95%). Os cargos que mais notificaram eventos do grupo de assistência direta ao paciente e de processo assistencial foram: coordenador de enfermagem e enfermeiro assistencial. Pode-se concluir que a notificação de eventos relacionados à assistência do paciente e envolvendo produtos de saúde é de fundamental importância dentro da instituição e contribui para a adoção de estratégias de prevenção de incidentes e melhoria da qualidade da assistência. A partir da pesquisa, foram elaborados dois produtos para serem adotados na instituição envolvida: a) Plano de Segurança do Paciente, de acordo com as exigências da RDC no 36 de 25 de julho de 2013 e b) Matriz de Gestão de Risco por unidade com base na metodologia do HFMEA.
Patient safety: analysis of event notifications in a private hospital
Keywords: Segurança; Paciente; Eventos; Notificações; Safety; Patient; Events; Notifications